Comparison of aesthetic outcome of different facial reconstruction techniques after resection of cutaneous squamous cell carcinoma. Issue 1 (January 2020) - Obermeier, Katharina; Smolka, Wenko
Abstract: Purpose: The aim of the study was to compare local and distant flaps for facial reconstruction after resection of cutaneous squamous cell carcinoma. Patients and method: Fifty patients with facial CSCC and subsequent facial reconstruction were retrospectively analysed. All complications such as wound infection, wound dehiscence, flap necrosis, partial or total flap loss were recorded. The aesthetic outcome was evaluated using colour prints of patients' photographs of different flaps in terms of skin colour, texture and scars by three judges. To compare the aesthetic outcome of distant and local flaps a Wilcoxon-Mann-Whitney-U-Test was applied. Results: The overall complication rate was low. Colour and texture of local flaps presented statistically significantly better results compared to distant flaps. There were no statistically significant differences between scars of local flaps and distant flaps (p = 0.528). A slight tendency was found showing scars of local flaps to be less visible than scars of distant flaps in defects extending in more than one facial aesthetic unit. Conclusion: Local flaps show statistically significant ly better aesthetic results compared to distant flaps in terms of colour and texture. Scars of local flaps seem to be slightly less visible compared to distant flaps in cases where defects were bridging more than one facial aesthetic unit. We conclude that local flaps should be preferred over free flaps whenever possible as far as the aesthetic outcome is concerned.